THE IMPLEMENTATION OF ACCOUNTING SYSTEM ON RAW MATERIALS PURCHASING AND CASH DISBURSEMENT TO SUPPORT THE INTERNAL CONTROL (Case Study at PR. Sejahtera Abadi Malang, Jawa Timur) - Adi Widiyanto (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
The purpose of this study was to know the implementation of accounting system on raw materials purchasing and cash disbursements, as well as internal control on raw materials purchasing and cash disbursements at PR. Sejahtera Abadi Malang. This study would explain the steps from implementation of accounting system on raw materials purchasing and cash disbursement to support the internal control. The research method in this research is by using descriptive research with a case study approach at PR. Sejahtera Abadi Malang. The result of the study was accounting system that implemented in the company, its found out some weaknesses in implementation of accounting system on raw materials purchasing and cash disbursement there are warehouse section didn’t separate with reception section, warehouse section didn’t use purchase requisition letter, and reception section didn’t make a goods receipt report. So basically the implementation of accounting system on raw materials purchasing and cash disbursement are needed improve to been effective and efficient. Keywords: Raw materials Purchasing, Cash disbursements, Intern Control Abstrak Tujuan dari penelitian ini adalah untuk mengetahui penerapan sistem akuntansi pada pembelian bahan baku dan pengeluaran kas, serta pengendalian intern pada pembelian bahan baku dan pengeluaran di PR Sejahtera Abadi Malang. Penelitian ini akan menjelaskan langkah-langkah dari penerapan sistem akuntansi pada pembelian bahan baku dan pengeluaran kas untuk mendukung pengendalian intern. Metode penelitian dalam penelitian ini adalah dengan menggunakan penelitian deskriptif dengan pendekatan studi kasus pada PR. Sejahtera Abadi Malang. Hasil dari penelitian ini adalah sistem akuntansi yang diterapkan di perusahaan, menemukan beberapa kelemahan pada penerapan sistem akuntansi pada pembelian bahan baku dan pengeluaran kas diantaranya bagian gudang tidak terpisah dengan bagian penerimaan, bagian gudang tidak menggunakan surat permintaan pembelian, dan bagian penerimaan tidak membuat laporan penerimaan barang. Jadi pada dasarnya penerapan sistem akuntansi pada pembelian bahan baku dan pengeluaran kas membutuhkan pengembangan agar menjadi efektif dan efisien. Kata Kunci : Pembelian Bahan Baku, Pengeluaran Kas, Pengendalian Intern.